2023
DOI: 10.1149/1945-7111/acf8fc
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Preparation of ZrFe2 and ZrFe1.8Ni0.2 Intermetallic Compounds by FFC Cambridge Process

Mohd. Sufiyan Khan,
Anwesha Mukherjee,
L. Shakila
et al.

Abstract: The aim of the present study was to prepare ZrFe2 and ZrFe1.8Ni0.2 intermetallic compounds by FFC Cambridge process. The intermetallic compounds were prepared directly from the mixed oxide precursors, namely ZrO2-Fe2O3 and ZrO2-Fe2O3-NiO, respectively. Electrochemical de-oxidation experiments were carried out with mixed oxide pellet cathode and HD graphite anode by applying a constant cell voltage of 3.1 V in CaCl2 melt at 900 oC. The electrochemical behaviour of oxides was studied by cyclic voltammetry using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The obtained cyclic voltammogram (not shown) was similar to our previous studies. 19 The calcium deposition and chlorine evolution onset potentials were observed at −2.25 V (vs Ni|NiO) and +0.98 V (vs Ni|NiO), respectively. There were no additional distinct current signatures apart from the calcium deposition and chlorine evolution, which indicated that the melt was free from redox-active impurities.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The obtained cyclic voltammogram (not shown) was similar to our previous studies. 19 The calcium deposition and chlorine evolution onset potentials were observed at −2.25 V (vs Ni|NiO) and +0.98 V (vs Ni|NiO), respectively. There were no additional distinct current signatures apart from the calcium deposition and chlorine evolution, which indicated that the melt was free from redox-active impurities.…”
Section: Resultsmentioning
confidence: 95%
“…10,11 The FFC Cambridge process has also been used for the preparation of various alloys and intermetallics, including hydrogen storage alloys (HSAs) such as TiFe, TiFe 0.4 Ni 0.6 , ZrCr 2 , ZrCr 0.7 Ni 0.3 , ZrMn 2 , ZrFe 2 , ZrFe 1.8 Ni 0.2 , LaNi 5 , La 0.5 Ce 0.5 Ni 5 , LaNi 4 Co, CeNi 5 , and TbNi 5 , from the mixed metal oxides. 9,[12][13][14][15][16][17][18][19][20][21] The main advantage of the FFC Cambridge process over the conventional arc-melting process is that it offers a more economical, feasible, and energy-efficient route for the preparation of these alloys and intermetallics. 22,23 In the FFC Cambridge process, a constant cell voltage is applied between a solid metal oxide cathode and a graphite anode, which results in the deoxidation of metal oxide.…”
mentioning
confidence: 99%